HTLV-I/II and blood donors: determinants associated with seropositivity in a low risk population HTLV-I/II e doadores de sangue: determinantes associados à soropositividade em população de baixo risco - Bernadette Catalan Soares; Anna Bárbara de F Carneiro Proietti; Fernando Augusto Proietti (Universidade de São Paulo, 2003)
OBJECTIVE: Blood donors in Brazil have been routinely screened for HTLV-I/II since 1993. A study was performed to estimate the prevalence of HTLV-I/II infection in a low risk population and to better understand determinants associated with seropositivity. METHODS: HTLV-I/II seropositive (n=135), indeterminate (n=167) and seronegative blood donors (n=116) were enrolled in an open prevalence prospective cohort study. A cross-sectional epidemiological study of positive, indeterminate and seronegative HTLV-I/II subjects was conducted to assess behavioral and environmental risk factors for seropositivity. HTLV-I/II serological status was confirmed using enzyme-linked immunosorbent assay (EIA) and Western blot (WB). RESULTS: The three groups were not homogeneous. HTLV-I/II seropositivity was associated to past blood transfusion and years of schooling, a marker of socioeconomic status, and use of non-intravenous illegal drugs. CONCLUSIONS: The study results reinforce the importance of continuous monitoring and improvement of blood donor selection process. OBJETIVO: Doadores de sangue no Brasil têm sido avaliados sorologicamente para o HTLV-I/II desde 1993. Assim, realizou-se estudo para estimar a prevalência dessa infecção em população de baixo risco e para melhor compreender os determinantes associados à soropositividade. MÉTODOS: Doadores de sangue soropositivos (n=135), soroindeterminados (n=167) e soronegativos (n=116) foram arrolados como participantes de uma coorte aberta e prevalente. Estudo transversal dos participantes desses três grupos avaliou fatores de risco comportamentais e ambientais para soropositividade. O status sorológico foi definido usando a reação de EIA (enzyme linked immunosorbent assay) e o teste Western blot (WB). RESULTADOS: Os três grupos apresentaram heterogeneidade entre si. A soropositividade mostrou-se associada à história pregressa de transfusão de sangue, em nível educacional, como um marcador de condição socioeconômica e ao uso de drogas ilegais não endovenosas. CONCLUSÕES: Os resultados confirmam a importância de um monitoramento e refinamento do processo de seleção dos doadores de sangue.